Bimetal-based catalyst as well as preparation method and application thereof

By using bimetallic-based catalyst RuCu/C in electrochemical method, the problem of low electrochemical reduction efficiency of carbon dioxide is solved, efficient methane synthesis is achieved, and the preparation process is simplified and the cost is reduced.

CN119307968APending Publication Date: 2025-01-14HUANENG CLEAN ENERGY RES INST
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411446244.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-14

Smart Images

  • Figure CN119307968A_ABST
    Figure CN119307968A_ABST
Patent Text Reader

Abstract

The invention provides a bimetallic-based catalyst as well as a preparation method and application thereof, and belongs to the technical field of electrochemistry. The preparation method comprises the following steps: adding carbon powder into ethylene glycol, uniformly mixing, adding a RuCl3 solution and a CuCl2 solution into the uniformly mixed solution, adjusting the pH value to be more than 10, and uniformly stirring and mixing to obtain a mixed solution; carrying out primary heating, cooling, centrifugation and freeze-drying treatment on the mixed solution to obtain a catalyst head product; and putting the initial product of the catalyst into a high-temperature tubular furnace, and carrying out secondary heating treatment in a flowing Ar / H2 atmosphere to obtain the RuCu / C catalyst. A polyol reduction method is adopted, ethylene glycol serves as a reducing agent and a surface active agent at the same time and reacts with metal salt under the high-temperature condition to generate nano-particles, the bimetallic nano-particles are deposited on a carbon substrate to form the RuCu / C catalyst, the catalyst has high activity on CO2 reduction through an electrochemical method, and the methane conversion efficiency is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of electrochemical technology, and specifically relates to a bimetallic catalyst and a preparation method and application thereof. Background Art

[0002] The electrocatalytic reduction of carbon dioxide into high-value-added fuels and chemicals provides a sustainable solution to energy and environmental issues. It can not only sustainably reduce the greenhouse effect and alleviate human society's dependence on fossil fuels, but also be suitable for existing distributed renewable energy power generation equipment due to its mild reaction conditions and fast start-stop characteristics. After more than ten years of research at home and abroad, the products of electrochemical carbon dioxide catalytic conversion now include: gas phase products: synthesis gas, methane, ethylene, ethane, propane, etc.; liquid phase products: formic acid, methanol, acetic acid, ethanol, propanol, isobutanol, etc.

[0003] Among the many products of carbon dioxide reduction, methane not only has the highest calorific value, but is also an important raw material for the manufacture of many chemical products including aromatics. In addition, as the main component of natural gas, methane has good compatibility with existing storage, distribution and consumption infrastructure. Therefore, highly selective electrochemical conversion of carbon dioxide to methane is an effective way to balance environmental and energy issues. The key step in the deep reduction of carbon dioxide to methane is the protonation of the CO* intermediate to produce CHO*. Its main competing reaction processes include the dimerization of CO* to produce dicarbon products and the direct desorption of the CO* intermediate from the catalyst surface to produce gaseous carbon monoxide. Therefore, the development of a catalyst for efficient activation and precise conversion of CO2 is the key to improving methane synthesis. Summary of the invention

[0004] The present disclosure aims to solve at least one of the technical problems existing in the prior art and to provide a bimetallic-based catalyst for electrochemical reduction of carbon dioxide to high value-added chemicals and a preparation method and application thereof.

[0005] In one aspect of the present disclosure, a method for preparing a bimetallic catalyst is provided, the preparation method comprising:

[0006] Add carbon powder to ethylene glycol and mix well, add RuCl3 solution and CuCl2 solution to the mixed solution, adjust the pH value to above 10, stir and mix well to obtain a mixed solution;

[0007] The mixed solution is subjected to a first heating, cooling, centrifugation and freeze-drying treatment to obtain a catalyst initial product;

[0008] The initial catalyst product is placed in a high-temperature tube furnace and subjected to a second heating treatment under a flowing Ar / H2 atmosphere to obtain a RuCu / C catalyst.

[0009] Optionally, the solid-liquid ratio of the carbon powder to the ethylene glycol is (1-3): 1 mg / mL.

[0010] Optionally, the content of the carbon powder is 40 to 60 parts by mass, and the volume of the ethylene glycol is 20 to 50 mL.

[0011] Optionally, the molar ratio of the RuCl3 solution to the CuCl2 solution is 1:1.

[0012] Optionally, the content of the RuCl3 solution and the CuCl2 solution is 0.05-0.15 mmol.

[0013] Optionally, the temperature of the second heating treatment is 170-190° C. and the time is 1.5-3 hours; and / or,

[0014] The temperature of the first heating treatment is 155-170° C. and the time is 1.5-3 hours.

[0015] In another aspect of the present disclosure, a bimetallic-based catalyst is provided, wherein the bimetallic-based catalyst is prepared by the preparation method described above.

[0016] Another aspect of the present disclosure provides an application of a bimetallic catalyst, wherein the bimetallic catalyst described above is used as an electrode in the electrochemical reduction of carbon dioxide to synthesize methane.

[0017] Optionally, the application process includes:

[0018] Adding the bimetallic catalyst to a mixed solution of tetrahydrofuran, 2-propanol and Nafion perfluororesin solution, and ultrasonically treating the mixture to form a mixed suspension;

[0019] The mixed suspension is dropped onto the surface of the electrode substrate to obtain an electrode.

[0020] Optionally, the solid-to-liquid ratio of the bimetallic catalyst to the tetrahydrofuran, the 2-propanol, and the Nafion perfluororesin solution is 1:(80-90):(90-100):(9-10) mg / μL.

[0021] The present disclosure proposes a bimetallic catalyst and its preparation method and application. The preparation method comprises: adding carbon powder to ethylene glycol and mixing, adding RuCl3 solution and CuCl2 solution to the mixed solution, adjusting the pH value to above 10, stirring and mixing, and obtaining a mixed solution; heating, cooling, centrifuging and freeze-drying the mixed solution for the first time to obtain a catalyst initial product; placing the catalyst initial product in a high-temperature tube furnace, and performing a second heating treatment under a flowing Ar / H2 atmosphere to obtain a RuCu / C catalyst. By adopting a polyol reduction method, ethylene glycol is used as a reducing agent and a surfactant at the same time in the preparation process, and nanoparticles are generated by reacting with metal salts under high temperature conditions, and the bimetallic nanoparticles are deposited on a carbon substrate to form a RuCu / C catalyst. The method is simple in process, easy to operate, and does not require the addition of multiple surfactants and reducing agents and other components. The catalyst has greater activity for the electrochemical CO2 reduction reaction and effectively improves the methane conversion efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a flowchart of a method for preparing a bimetallic-based catalyst according to an embodiment of the present disclosure;

[0023] Figure 2 A flowchart of forming an electrode material for a bimetallic-based catalyst according to another embodiment of the present disclosure;

[0024] Figure 3 This is a transmission electron microscope image of the bimetallic-based catalyst material of Example 1 of the present disclosure;

[0025] Figure 4 This is the X-ray diffraction result of the bimetallic-based catalyst material of Example 1 of the present disclosure;

[0026] Figure 5 is a current density-voltage curve diagram of Example 1 of the present disclosure;

[0027] Figure 6 This is a methane conversion efficiency-voltage curve diagram of Example 1 of the present disclosure. DETAILED DESCRIPTION

[0028] In order to enable those skilled in the art to better understand the technical solution of the present disclosure, the present disclosure is further described in detail below in conjunction with the accompanying drawings and specific implementation methods. It should be understood that the specific embodiments described herein are only used to explain the present disclosure and are not used to limit the disclosure. The described embodiments are part of the embodiments of the present disclosure, rather than all of the embodiments. Based on the described embodiments of the present disclosure, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present disclosure.

[0029] like Figure 1As shown, in one aspect of the present disclosure, a method S100 for preparing a bimetallic catalyst is provided, comprising steps S110 to S130:

[0030] S110, adding carbon powder to ethylene glycol and mixing, adding RuCl3 solution and CuCl2 solution to the mixed solution, adjusting the pH value to above 10, stirring and mixing to obtain a mixed solution.

[0031] Specifically, carbon powder was added to ethylene glycol and ultrasonically treated for 30 minutes to mix the carbon powder and ethylene glycol evenly. Then, RuCl3 solution and CuCl2 solution were weighed and directly injected into the mixed solution. The pH value was adjusted and stirred for 0.5-1.5 hours until the mixture was evenly mixed to obtain a mixed solution.

[0032] It should be noted that the present embodiment does not specifically limit the substance for adjusting the pH value of the solution, for example, KOH, NaOH, etc.

[0033] It should be further explained that the present embodiment does not impose any specific limitation on the particle size of the carbon powder. For example, nano-sized carbon nanoparticles may be used as a substrate to facilitate the deposition of the subsequently generated bimetallic nanoparticles.

[0034] It should be noted that the present embodiment does not impose any specific limitation on the contents of carbon powder and ethylene glycol, as long as the carbon powder can be evenly mixed in the ethylene glycol and the metal nanoparticle deposition requirements can be met.

[0035] In some preferred embodiments, the solid-liquid ratio of carbon powder to ethylene glycol is (1-3):1 mg / mL, for example, 1:1, 2:1, 3:1, etc.

[0036] As a further preferred embodiment, the content of carbon powder is 40 to 60 parts by mass, for example, 40 mg, 50 mg, 60 mg, etc., and the volume of ethylene glycol is 20 to 50 mL, for example, 20 mL, 30 mL, 40 mL, 50 mL, etc.

[0037] In this embodiment, carbon powder is used as a carrier of metal nanoparticles, so that the metal particles are uniformly deposited on the carbon powder matrix. Secondly, ethylene glycol is used as a reducing agent and a surfactant at the same time, reacting with metal salts under high temperature conditions to generate bimetallic nanoparticles RuCu nanoparticles. At the same time, the bimetallic nanoparticles are deposited on the carbon nanoparticle substrate, effectively simplifying the reaction components and the preparation process.

[0038] In other preferred embodiments, the molar ratio of RuCl3 solution to CuCl2 solution is 1:1.

[0039] As a further preferred embodiment, the content of RuCl3 solution and CuCl2 solution is 0.05-0.15 mmol, for example, the content of RuCl3 solution is preferably 0.1 mmol, and the content of CuCl2 solution is preferably 0.1 mmol.

[0040] S120, heating, cooling, centrifuging and freeze-drying the mixed solution for the first time to obtain a catalyst initial product.

[0041] It should be noted that the present embodiment does not specifically limit the heating method of the mixed solution. For example, the mixed solution may be heated in a silicone oil bath. Of course, those skilled in the art may also use other heating methods to heat the mixed solution.

[0042] Specifically, the mixed solution obtained in step S110 is heated to 155-170° C. in a silicone oil bath and maintained for 1.5-3 hours. After natural cooling, the mixture is centrifuged with a large amount of acetone and water, and then freeze-dried to obtain a catalyst initial product.

[0043] In some preferred embodiments, the temperature of the first heating treatment is 155°C, 160°C, 165°C, and the time is preferably 1.5h, 2h, 2.5h, 3h, etc.

[0044] S130, placing the initial catalyst product in a high-temperature tube furnace, and performing a second heating treatment under a flowing Ar / H2 atmosphere to obtain a RuCu / C catalyst.

[0045] Specifically, the above-mentioned initial catalyst product is finally placed in a high-temperature tube furnace, heated to 170-190° C. in a flowing Ar / H2 atmosphere, and maintained for 1.5-3 hours to remove possible organic residues to obtain a RuCu / C catalyst.

[0046] In some preferred embodiments, the temperature of the second heating treatment is 170° C., 180° C., 190° C., and the time is 1.5 h, 2 h, 3 h, etc.

[0047] In this embodiment, a polyol reduction method is adopted, in which ethylene glycol is used as both a reducing agent and a surfactant during the preparation process, and nanoparticles are generated by reacting with metal salts under high temperature conditions. This method is simple in process, easy to operate, and does not require the addition of multiple surfactants, reducing agents and other components.

[0048] In another aspect of the present disclosure, a bimetallic catalyst is provided. The catalyst is prepared by the preparation method described above. For the specific preparation process, please refer to the above description and will not be repeated here.

[0049] The catalyst material prepared in this embodiment is a bimetallic material deposited on a carbon nano-substrate, which has a high activation efficiency for carbon dioxide and can accurately convert it into methane.

[0050] Combined Figure 3 As shown, according to the transmission electron microscopy results of the bimetallic-based catalyst, RuCu nanoparticles with an average radius ranging from a few nanometers to tens of nanometers are uniformly deposited on the carbon nanoparticle substrate, which shows that RuCu nanoparticles have been successfully prepared and distributed on the carbon substrate to form a RuCu / C catalyst.

[0051] Furthermore, combined with Figure 4 As shown, according to the X-ray diffraction of the bimetallic-based catalyst, the carbon nanoparticles as the substrate only show the (002) crystal phase, and the prepared RuCu / C catalyst shows the (100)(101)(102)(110)(103) crystal phase, which indicates that the RuCu / C catalyst is prepared in this embodiment.

[0052] Another aspect of the present disclosure provides an application of a bimetallic-based catalyst, wherein the bimetallic-based catalyst described above is used in an electrode.

[0053] like Figure 2 As shown, the application process S200 includes the following specific steps S210 to S220:

[0054] S210, adding the bimetallic catalyst to a mixed solution of tetrahydrofuran, 2-propanol and Nafion perfluororesin solution, and ultrasonically treating the mixture to form a mixed suspension.

[0055] In some preferred embodiments, the solid-liquid ratio of the bimetallic catalyst to the tetrahydrofuran, the 2-propanol, and the Nafion perfluororesin solution is 1:(80-90):(90-100):(9-10) mg / μL, for example, 1:90:100:10, etc.

[0056] As a further preferred embodiment, the content of the bimetallic catalyst may be preferably 4-6 mg, and correspondingly, the content of tetrahydrofuran may be preferably 360-540 mL, the content of 2-propanol may be preferably 400-600 mL, and the content of Nafion perfluororesin solution may be preferably 40-60 mL.

[0057] As a further preferred embodiment, the content of the bimetallic catalyst may be preferably 5 mg, and correspondingly, the content of tetrahydrofuran may be preferably 450 mL, the content of 2-propanol may be preferably 500 mL, and the content of Nafion perfluororesin solution may be preferably 50 mL.

[0058] It should be noted that the Nafion perfluorinated resin solution may be a Nafion perfluorinated resin solution with a concentration of 5 wt %, which can further improve the carbon dioxide capture capability.

[0059] In other preferred embodiments, the ultrasonic treatment time ranges from 20 to 40 minutes.

[0060] As a further preferred embodiment, the ultrasonic treatment time is preferably 30 minutes.

[0061] S220, dropping the mixed suspension onto the surface of the electrode substrate to obtain an electrode.

[0062] It should be noted that the present embodiment does not specifically limit the manner in which the suspension is added dropwise to the surface of the electrode substrate. For example, the suspension is added dropwise to the surface of the electrode substrate so that the suspension is more evenly coated on the electrode.

[0063] When the bimetallic-based catalyst of this embodiment is applied to the electrochemical reduction reaction of carbon dioxide, the RuCu / C catalyst has greater activity for the electrochemical CO2 reduction reaction, which helps to promote the conversion of carbon dioxide into methane, thereby improving the conversion rate of methane.

[0064] It should be further explained that the present embodiment does not specifically limit the type of the electrode substrate, for example, carbon paper, carbon cloth, carbon felt, etc.

[0065] In some preferred embodiments, the carbon paper may preferably be AvCarb MGL190, MGL370, MGL280, and the like.

[0066] It should be noted that the present embodiment does not specifically limit the size of the electrode substrate, for example, 1×1 cm 2 Of course, for those skilled in the art, other sizes of base materials can also be set.

[0067] The preparation method and application of the bimetallic catalyst will be further described below in conjunction with several specific examples:

[0068] Example 1

[0069] The preparation method of the bimetallic catalyst in this example includes the following steps:

[0070] S1. Add 50 mg of carbon powder to 25 mL of ethylene glycol and mix well by ultrasonication for 30 minutes. Weigh 0.1 mmol of RuCl3 and 0.1 mmmol of CuCl2 solution and inject them directly into the above solution. Adjust the pH value to above 10 by adding dissolved KOH tablets, and continue stirring for 1 hour until the mixture is well mixed.

[0071] S2. The mixture prepared in S1 was heated to 160°C in a silicone oil bath and maintained for 2 hours. After natural cooling, the mixture was centrifuged with a large amount of acetone and water, freeze-dried, and then placed in a high-temperature tube furnace and heated to 180°C in a flowing Ar / H2 atmosphere for 2 hours to remove residual organic matter, thereby obtaining a RuCu / C catalyst.

[0072] like Figure 3 As shown, the average radius of the RuCu nanoparticles ranges from several nanometers to tens of nanometers, and the RuCu nanoparticles are uniformly deposited on the carbon nanoparticle substrate.

[0073] like Figure 4 As shown, the carbon nanoparticles as the substrate only show the (002) crystal phase, as Figure 4 The black lines in the figure show that the RuCu / C catalyst obtained in this example shows a (100)(101)(102)(110)(103) crystalline phase, which indicates that RuCu nanoparticles were successfully prepared and deposited on carbon nanoparticles to form a RuCu / C catalyst.

[0074] Further, coating the obtained catalyst on the electrode surface comprises:

[0075] 5 mg of the prepared RuCu / C catalyst material was added to 450 μL of tetrahydrofuran, 500 μL of 2-propanol and 50 μL of a 5 wt% Nafion perfluororesin mixed solution, and a uniform mixed suspension solution was formed after ultrasonication for 30 minutes. The suspension solution was added dropwise onto AvCarb MGL370 carbon paper (1×1 cm 2 ) surface, thereby preparing the electrode material.

[0076] Furthermore, the present embodiment also uses the electrode material in electrochemistry, and the electrochemical test is performed by a three-electrode system, wherein the working electrode is the prepared electrode material, the reference electrode is an Ag / AgCl / sat.KCl electrode, the counter electrode is a Pt mesh, and the electrolyte is a 0.1M KHCO3 solution. Figure 5 As shown, by linear sweep voltammetry test, sweeping from 0.5V vs RHE to -0.6V vs RHE, it was found that the current density of RuCu / C catalyst in CO2 atmosphere was much greater than that in the inert atmosphere of Ar, indicating that RuCu / C catalyst has great activity for electrochemical CO2 reduction reaction.

[0077] Furthermore, this example also uses the carbon electrode as the working electrode for comparative testing. Please continue to refer to Figure 5The current density of the carbon electrode in a CO2 atmosphere is slightly greater than that in an inert Ar atmosphere, but is less than the current density of the RuCu / C catalyst in a CO2 atmosphere and an Ar atmosphere. This indicates that the RuCu / C catalyst prepared in Example 1 has a high activity towards carbon dioxide when used on an electrode, which helps to improve the efficiency of methane synthesis.

[0078] Furthermore, electrochemical CO2 reduction tests were performed in constant current mode, such as Figure 6 As shown in the figure, as the potential is gradually reduced from -0.2V to -0.6V vs RHE, the electrokinetics gradually improves, and thus the methane yield also increases. Among them, under the condition of -0.3V vs RHE, the selectivity of methane reaches the maximum, which is 97%.

[0079] Comparative Example 1

[0080] In this example, no bimetallic catalyst was added to the electrode, and the methane synthesis rate results were as follows:

[0081] 450 μL of tetrahydrofuran, 500 μL of 2-propanol and 50 μL of 5 wt% Nafion perfluororesin were mixed and ultrasonicated for 30 minutes to form a uniform mixed suspension solution. The suspension solution was added dropwise onto AvCarb MGL370 carbon paper (1×1 cm 2 ) surface, thereby preparing electrode materials, which are used in electrochemistry. The electrochemical test is carried out through a three-electrode system. In the electrochemical CO2 reduction test under constant current mode, the selectivity of methane is only 51%. This shows that the bimetallic catalyst has greater activity in the electrochemical CO2 reduction and helps to improve the yield of methane.

[0082] The present disclosure provides a bimetallic catalyst and its preparation method and application, which have the following beneficial effects:

[0083] First, the present invention adopts a polyol reduction method, using ethylene glycol as both a reducing agent and a surfactant, to react with a metal salt under high temperature conditions to generate nanoparticles, and RuCu nanoparticles are uniformly deposited on a carbon nanoparticle substrate to form a RuCu / C catalyst. The preparation process is simple, the required raw materials are simple, and the cost is low.

[0084] Second, the RuCu / C catalyst disclosed in the present invention has great activity in the electrochemical CO2 reduction reaction, and can reduce it to high value-added chemicals, effectively improving the synthesis efficiency of methane.

[0085] It is to be understood that the above embodiments are merely exemplary embodiments used to illustrate the principles of the present disclosure, but the present disclosure is not limited thereto. For those of ordinary skill in the art, various modifications and improvements can be made without departing from the spirit and substance of the present disclosure, and these modifications and improvements are also considered to be within the scope of protection of the present disclosure.

Claims

1. A method for preparing a bimetallic catalyst, characterized in that: The preparation method comprises: Add carbon powder to ethylene glycol and mix well, add RuCl3 solution and CuCl2 solution to the mixed solution, adjust the pH value to above 10, stir and mix well to obtain a mixed solution; The mixed solution is subjected to a first heating, cooling, centrifugation and freeze-drying treatment to obtain a catalyst initial product; The initial catalyst product is placed in a high-temperature tube furnace and subjected to a second heating treatment under a flowing Ar / H2 atmosphere to obtain a RuCu / C catalyst.

2. The preparation method according to claim 1, characterized in that: The solid-liquid ratio of the carbon powder to the ethylene glycol is (1-3): 1 mg / mL.

3. The preparation method according to claim 2, characterized in that: The content of the carbon powder is 40 to 60 parts by mass, and the volume of the ethylene glycol is 20 to 50 mL.

4. The preparation method according to claim 1, characterized in that: The molar ratio of the RuCl3 solution to the CuCl2 solution is 1:

1.

5. The preparation method according to claim 4, characterized in that: The content of the RuCl3 solution and the CuCl2 solution is 0.05-0.15 mmol.

6. The preparation method according to claim 1, characterized in that: The second heating treatment is performed at a temperature of 170 to 190° C. for a time of 1.5 to 3 hours; and / or, The temperature of the first heating treatment is 155-170° C., and the time is 1.5-3 hours.

7. A bimetallic catalyst, characterized in that: The bimetallic-based catalyst is prepared by the preparation method described in any one of claims 1 to 6.

8. A bimetallic catalyst as claimed in claim 7 used in an electrode for electrochemical reduction of carbon dioxide to synthesize methane.

9. The use according to claim 8, characterized in that: The application process includes: Adding the bimetallic catalyst to a mixed solution of tetrahydrofuran, 2-propanol and Nafion perfluororesin solution, and ultrasonically treating the mixture to form a mixed suspension; The mixed suspension is dropped onto the surface of the electrode substrate to obtain an electrode.

10. The use according to claim 9, characterized in that: The solid-to-liquid ratio of the bimetallic catalyst to the tetrahydrofuran, the 2-propanol, and the Nafion perfluororesin solution is 1:(80-90):(90-100):(9-10) mg / μL.